Intra-individual variation of HRV during orthostatic challenge in elite male field hockey players - Vescovi, J. D. (Journal of Medical Systems, 2019)
The purpose of this study was to examine the intra-individual variation of heart rate variability (HRV) and heart rate using an orthostatic challenge in elite male athletes during a training camp. Heart rate (variability) was measured upon waking. Log-transformed HRV metrics were evaluated in three segments (first min discarded for stabilization): 0-3 min supine, 3-6 min supine, and standing. Heart rate was assessed while supine, 15 s after standing and average final 30 s standing (Rusko protocol). A RM-ANOVA compared intra-individual means, standard deviations (SD) and coefficients of variation (CV%) for HRV and heart rate. The intraclass correlation coefficient (ICC) and standard error of measurement (SEmeas) were used for relative and absolute reliability, respectively. Time and frequency domain HRV metrics had low variation (CV% <8.5%; SEmeas% =4.0%) for 0-3 min supine which was not improved during 3-6 min. Standing HRV had lower ICC and higher SEmeas than supine values. Variability and reliability outcomes for heart rate were comparable to log-transformed HRV metrics. This study uniquely describes the intra-individual variation of HRV metrics during an orthostatic challenge and demonstrated low variability in this cohort of elite male athletes. These data can be helpful for identifying when true individual changes occur for the autonomic nervous system indices in supine and standing positions.